2011
DOI: 10.1073/pnas.1117500108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the differential use of glucose and glutamine in cell proliferation as revealed by synchronized HeLa cells

Abstract: During cell division, the activation of glycolysis is tightly regulated by the action of two ubiquitin ligases, anaphase-promoting complex/ cyclosome-Cdh1 (APC/C-Cdh1) and SKP1/CUL-1/F-box protein-β-transducin repeat-containing protein (SCF-β-TrCP), which control the transient appearance and metabolic activity of the glycolysispromoting enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase, isoform 3 (PFKFB3). We now demonstrate that the breakdown of PFKFB3 during S phase occurs specifically via a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
140
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 31 publications
15
140
0
Order By: Relevance
“…The present results suggest further investigation of the functional roles of glycolytic enzymes in mitochondria and the nucleus is needed, especially in the light of indications that they concentrate in the MAM region of mitochondria 84 and that mitochondrial restructuring and bioenergetic plasticity are also important for stem cell differentiation/regression. 96 Both PKM2 97,98 and PFKFB3 74 have recently been proposed as "master" proteins for controlling the metabolic changes involved in hypoxia, proliferation and cancer, but a substantial body of other literature and the present results suggest that much more complicated networks with feedback loops involving many glycolysis, TCAcycle, OxPhos and signaling proteins may be involved. Furthermore hypoxia causes dynamic changes in protein subcellular location involving functions that go far beyond changes in glycolysis and include TCA-cycle, OxPhos and chromatin remodeling proteins among many others.…”
Section: Potential Connections To Cancermentioning
confidence: 79%
See 2 more Smart Citations
“…The present results suggest further investigation of the functional roles of glycolytic enzymes in mitochondria and the nucleus is needed, especially in the light of indications that they concentrate in the MAM region of mitochondria 84 and that mitochondrial restructuring and bioenergetic plasticity are also important for stem cell differentiation/regression. 96 Both PKM2 97,98 and PFKFB3 74 have recently been proposed as "master" proteins for controlling the metabolic changes involved in hypoxia, proliferation and cancer, but a substantial body of other literature and the present results suggest that much more complicated networks with feedback loops involving many glycolysis, TCAcycle, OxPhos and signaling proteins may be involved. Furthermore hypoxia causes dynamic changes in protein subcellular location involving functions that go far beyond changes in glycolysis and include TCA-cycle, OxPhos and chromatin remodeling proteins among many others.…”
Section: Potential Connections To Cancermentioning
confidence: 79%
“…Very recently, connections to the cell cycle have been established for nuclear FBP1 72 and PGAM1 in the nucleus of cancer cells has been observed. 73 This is also the case for fructose-2,6-biphosphatase 3 (PFKFB3) 74 which, although not a direct participant in the glycolysis enzymatic cascade, has major effects on glycolysis through the allosteric regulator fructose 2,6-bisphosphate that apparently include variations in cellular energy source (glutamine vs glucose) as a function of the cell cycle in cancer cells. 74,75 There are scattered experimental reports of further functions of these and other glycolytic enzymes in the nucleus, mitochondria and elsewhere in cells (Supporting Information Table 5).…”
Section: Proteins Involved In Glycolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, many cancer cells are ''glutamine addicted,'' and require exogenous glutamine to support survival and proliferation (95). For example, cell cycle progression in HeLa cells is absolutely dependent on glutamine (29). Jeong et al showed that genotoxic stress, which arrests cell cycle progression to allow DNA damage repair, induces SIRT4 expression, which, in turn, represses mitochondrial glutamine metabolism (71).…”
Section: Sirt4 Acts As a Tumor Suppressor Via Repression Of Glutaminementioning
confidence: 99%
“…1A). 10 Whether this relates to the use of glutamine for the production of biomass, redox homeostasis and/or energy requires further study.…”
Section: Introductionmentioning
confidence: 99%